Vegetation dynamics of canopy tree species of Lendrikia Reserve Forest, Kandhamal, Odisha, India - ANITA DASH; RABINDRA KUMAR MISHRA; BIDYUT KUMAR PATRA; ASHIS KUMAR DASH; ADITI SAHU; ANIL KUMAR BISWAL; VEERENDRA PRATAP UPADHYAY (Society for Indonesian Biodiversity, 2026)
Abstract. Dash A, Mishra RK, Patra BK, Dash A, Sahu A, Biswal AK, Upadhyay VP. 2026. Vegetation dynamics of canopy tree species of Lendrikia Reserve Forest, Kandhamal, Odisha, India. Biodiversitas 27 (2): d270217. https://doi.org/10.13057/biodiv/d270217. Sustainable management of forests, especially tropical forests, is essential to comprehend how the phytosociological attributes and diversity indices of canopy tree species affect forest structure and to propose forest management options. The moist deciduous forest covers of Lendrikia Reserve Forest (LRF), an ecologically sensitive and biodiverse area in Phulbani Forest Division, Kandhamal, Odisha, India, have not yet been assessed, though numerous studies have been conducted in various tropical forest covers of India and Odisha. To address this knowledge gap, we examined phytosociological attributes of canopy tree species in the tropical moist deciduous forests of LRF in Phulbani Forest Division. Forty quadrats (20 m × 20 m) were randomly laid within the reserve forest for the study. A total of 70 canopy tree species from 55 genera and 23 families was recorded. Across species, the basal area of the species ranged from 0.233 to 2.66 m² ha-¹, totalling to 27.6 m² ha-¹, and the density from 0.625 to 43.75 individuals ha⁻¹, totalling to 575 individuals ha-¹. The Shannon wiener diversity, evenness, richness, concentration of dominance, and beta diversity of species were 3.92, 0.92, 10.11, 0.26, and 6.65, respectively, indicating the heterogeneous nature of the reserve forest. In terms of Importance Value Index (IVI), Shorea robusta (17.74) was the most dominant tree species, followed by Ficus religiosa (10.51), Terminalia anogeissiana (9.24), Schleichera oleosa (8.67), Melia azedarach (8.41), and Lannea coromandelica (8.31) as co-dominants. The conservation status of tree species of the reserve, as per the IUCN Red list category, includes vulnerable (04), critically endangered (01), endangered (01), and near-threatened species (02). The present study emphasizes that the combined knowledge of phytosociological characters, along with documentation of the conservation status of canopy tree species, is essential for prioritizing conservation efforts for managing resources and ensuring the long-term sustainability of both the plant species and the forest ecosystem.